1989
DOI: 10.1017/s0003356100032736
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the welfare and carcass and meat quality of pigs 2. Mixing unfamiliar pigs

Abstract: Mixing pigs from different social groups is known to cause turmoil which often results in skin lacerations as well as dark, firm and dry meat. Nine hundred and sixty commercial crossbred pigs were used for this experiment, divided into eight consignments. Within each consignment the pigs were divided into groups of about 15. The pigs in each group had coexisted for at least 6 weeks prior to slaughter. Thirty min before loading for slaughter, groups of pigs were either mixed with unfamiliar pigs or not mixed. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 5 publications
0
24
0
2
Order By: Relevance
“…In this study, climbing behaviour was observed more often than turning around at this stage, as a result of the combined effect of electric goading and reduced space allowance. It is well documented that when space is decreased, turning around is limited and pigs try to escape from the stressor (the electrical shock and the handler in this study) by climbing over the backs of other pen mates in search of protection within the group (Guise and Penny 1989;Lambooj and Engel 1991).…”
Section: Agonistic Acts Fightmentioning
confidence: 77%
“…In this study, climbing behaviour was observed more often than turning around at this stage, as a result of the combined effect of electric goading and reduced space allowance. It is well documented that when space is decreased, turning around is limited and pigs try to escape from the stressor (the electrical shock and the handler in this study) by climbing over the backs of other pen mates in search of protection within the group (Guise and Penny 1989;Lambooj and Engel 1991).…”
Section: Agonistic Acts Fightmentioning
confidence: 77%
“…Pre-slaughter fasting without mixing results in a low frequency of skin blemishing due to fighting, whereas mixing, with or without fasting, has a substantial negative effect on the frequency of skin blemish scores (Murray and Jones 1994;Warriss 1996;Guise and Penny 1989). Although not always commercially practical, the extent of fighting due to mixing can be minimised by keeping pigs in small groups (Barton-Gade et al 1996), by optimising stocking density and by limiting the length of lairage at the abattoir (Geverink et al 1996).…”
Section: Carcass Skin Damagementioning
confidence: 99%
“…Each week pigs from at least two of the three genotypes were allocated to each For personal use only. Mixing (Guise and Penny 1989;Karlsson and Lundstrom 1992) and fasting (Jones et al 1985;Fischer et al 1986;Murray et al 1989;Eikelenboom at al. 1991) …”
Section: Animals and Designmentioning
confidence: 99%
“…Yet, the pH at 45 min post-slaughter, the colour and the drip loss of the longissimus muscle were unaffected. Guise and Penny (1989) found that Fibre Optic Probe (FOP) values were not affected by mixing prior to shipping from the farm or after arriving at the abattoir, whereas mixing prior to leaving the farm increased the frequency of skin blemishes.…”
mentioning
confidence: 99%